Analysis of the Effect of Surgical Treatment for the Patients with Hirayama Disease from the Perspective of Cervical Spine Sagittal Alignment - Song, Jian; Cui, Zhong-Yi; Chen, Zhen-Hao; Jiang, Jian-Yuan (World neurosurgery, 2020)
This study was carried out to analyze the surgical effect of cervical spine sagittal alignment for patients with Hirayama disease (HD). Forty-four subjects were retrospectively analyzed for the parameters of cervical spine sagittal alignment. The case group consisted of 23 patients with HD, whereas the control group consisted of 21 healthy adolescent subjects. Pre- and postoperative cervical spine sagittal parameters of the patients with HD were collected; the cervical sagittal parameters of the healthy adolescent subjects were also collected. Sagittal alignment parameters were compared between the patients with HD and the healthy adolescent subjects, and between the pre- and postoperative parameters for the patients with HD. Forty-four subjects completed the follow-up, with the average follow-up period being 18.0 months. No significant differences were detected between the HD and control groups for clinical parameters (P > 0.05). The preoperative HD group had smaller values compared with the control group in the sagittal parameters of C2-7 cervical lordosis (CL) angle, T1 slope, thoracic inlet angle (TIA), and cervical tilt angle (P < 0.05). For the patients with HD, the preoperative values were smaller compared with the postoperative HD values for the parameters of C2-7 CL angle, T1 slope, and cervical tilt angle (P < 0.05). We found no significant differences between the postoperative patients with HD and the healthy subjects, including C2-7 CL angle, C2-7 sagittal vertical axis, T1 slope, TIA, neck tilt angle, cervical tilt angle, and cranial tilt angle (P > 0.05). Patients with HD have sagittal imbalance of the cervical spine compared with age-matched healthy adolescent subjects, and surgical treatment could correct the sagittal imbalance.